Smoking, the HLA-DRB1 shared epitope and ACPA fine-specificity in Koreans with rheumatoid arthritis: evidence for more than one pathogenic pathway linking smoking to disease. Issue 4 (16th March 2013) - Fisher, Benjamin A; Bang, So-Young; Chowdhury, Muslima; Lee, Hye-Soon; Kim, Jae-Hoon; Charles, Peter; Venables, Patrick; Bae, Sang-Cheol
Abstract : Objectives: Data from North European rheumatoid arthritis (RA) populations has suggested a particularly strong association of gene-environment interaction between smoking and HLA-DRB1 shared epitope (SE) with antibodies to citrullinated α-enolase (CEP-1) and vimentin (cVim) peptides. We investigated this further by examining anticitrullinated peptide/protein antibody (ACPA) fine specificity in a Korean cohort, where there are notable differences in the RA-associated HLA-DRB1 alleles. Methods: Antibodies to fibrinogen (cFib), α-enolase (CEP-1) and vimentin (cVim) peptides and cyclic citrullinated peptide (CCP) were measured in 513 cases. The Mann-Whitney U test was used to compare antibody levels. Logistic regression generated ORs for RA in a case-control analysis with 1101 controls. Association of ACPA status and erosion in patients with RA was examined by logistic regression. Results: Anti-CCP, CEP-1, cVim and fibrinogen peptides were found in 86.7%, 63.9%, 45.5% and 74.7%, respectively. The number of ACPA and their levels were associated with SE, with evidence of a gene-dosage effect. There was a particular association of smoking with levels of anti-CEP-1. However, a gene-environment interaction was associated with all the ACPA positive subgroups, albeit the highest OR was seen with the anti-CCP+/cVim+ subset. In the absence of SE, smoking only conferred risk for anti-CCP negative subsets. The presence of erosions was not associated with the number of positive ACPA or specificity. Conclusions: The SE governed the magnitude and diversity of the ACPA response, but its interaction with smoking did not exclusively segregate with any of the ACPA specificities studied here. Smoking was associated with RA by SE-dependent and independent effects.